Criminalization of the Purchase of Sexual Services - บรรพหาร บุญญาพร (Huachiew Chalermprakiet Law Journal, 2020)
This research aims to study the guidelines for the creation of legal measures to take offense to the sex service buyer and study the measures of law enforcement by the government officials for optimum performance. By doing a study the laws and procedures from Sweden and study the methods of punishment against offenders of sexual service from France, including study the methods of criminalize the buyer of sexual service on internet from America. The study also analyse the problems of Thai society in the matter of sexual service trade to provide guidance on how to propose relevant laws to the context of Thailand. According to the studies, it has been found that Thailand has no criminal law to criminalized the sex service buyers. But, there is a criminal law in the matter of sexual assault which is only applies to people who are under 18 years of age to be able to apply for sexual service buyers. There are also criminal laws against sexual service traders in some cases. In addition, the law enforcement by government officials still has many problems such as corruption, insufficient budget and experience problems with influential people. This is why the sexual service problems in Thailand cannot be accomplished. Therefore, Thailand should create criminal legal measures to punish the sex service buyers and should see the penalties for those who commit to the sexual service to make the most benefit for the society. And should create a campaign to raise the awareness of society as well as government officials to see the importance of such issues.